THE MULTIPLE TECHNIQUES CORRELATED WITH STUDENTS’ ENGLISH WRITING OUTCOME AND THEIR LEARNING PERCEPTION - Eka Pra Setiyawati (Premise: Journal of English Education and Applied Linguistics, 2017)
Some studies have discussed about the specific technique in teaching English, especially in writing skill. The results indicated that the conducted technique had some influences or even correlations with students’ writing outcome. However, the studies just focused on examining one or two techniques. In this study, the author aimed to assemble some techniques she has applied in English writing class to be correlated with the students’ outcome and learning perception. The research questions are ; 1. What was the students’ English writing outcome taught by multiple techniques?, 3. How did the students’ perception about the multiple techniques?, 4. Are there any correlation of those techniques and the students’ writing outcome and learning perception?. There were about 25 students of class twelve Ibnu Shina at Senior High School MA Ma’arif 06 Pasir Sakti as subjects in the study. Upon this study, it can be concluded that the multiple techniques which have been applied in the classroom are correlated with the students’ writing outcome and their learning perception. English teachers are suggested to apply more than two techniques for particular skill and need in order to reach the maximum achievement of learning a foreign language.